Integrating Learning Media for Language and Literacy Development: Educational Impact and Economic Evaluation of Recycled Paper Production - Aliyyah, Rusi Rusmiati; Roestamy, Martin; Fauziah, Siti Pupu; Suherman, Irman; Kholik, Abdul; Warizal, Warizal (International Journal of Language Education, 2025)
This study investigates the development and integration of literacy tree learning media as an innovative educational tool for enhancing language and literacy development among elementary school students. The research emphasizes the role of literacy tree learning media in promoting reading, writing, and language comprehension within classroom settings. Alongside its pedagogical benefits, the study includes an economic evaluation of producing the literacy tree learning media using recycled paper, highlighting both its cost-effectiveness and environmental sustainability. The economic assessment covers key factors such as production costs, labor, and material expenses, demonstrating that literacy tree learning media offers a practical, affordable, and sustainable solution for educational institutions. By combining educational innovation with economic feasibility, this study provides valuable insights for schools seeking to improve literacy and language outcomes while contributing to resource conservation and environmental responsibility